Examination of the Prognostic Factor of Femoral Neck Fracture in Elderly Patients and Cases with Poor Prognosis - SHINTO Yoshitaka; 田中 森男; 田中 治; 荒木 信人; 内田 淳正; 小野 啓郎 (Japanese Journal of Rheumatism and Joint Surgery, 1991)
A follow-up study was made of 83 patients from 70 to 99 years old (average; 82.2) with femoral neck fracture. Thirteen patients were male, and 70 female. The duration of follow-up was at least one year. As the purpose was to examine the prognostic factor of femoral neck fracture in the aged, we investigated the relation between several factors (patient's age, degree of dementia, methods of operation, preoperative walking ability, osteoporosis and complications) and post-operative walking ability. Patients with poor prognosis were also analyzed. The most important factors affecting prognosis were the degree of dementia and complications. Eighteen patients with poor prognosis had died of such things as pneumonia, heat failure and renal dysfunction. These results suggest that the prevention of both dementia and complications are important for the improvement of prognosis in the patient with femoral neck fracture.